Two Cases of Morel-Lavallée Lesion Which Resulted in a Wide Skin Necrosis from a Small Laceration - Tadahiro Nakajima; Kaoru Tada; Mika Nakada; Masashi Matsuta; Hiroyuki Tsuchiya (Case Reports in Orthopedics)
Morel-Lavallée lesion (MLL) is a degloving injury in soft tissues caused by shear force accompanying trauma. Even if it is a small lacrimal wound at the initial visit, there is a range of skin necrosis which is not suitable for it. As a cause of the injury, a shearing force was applied over a wide range, and penetrating blood vessel damage to the skin occurred, resulting in skin necrosis. Attention is required.